Effect of ultrasonic welding conditions and energy director thickness on structure and properties of lap-joints of PEEK-based composites reinforced with short carbon fibers (Fracture and Structural Integrity, 2026)
The aim of this study was to investigate the effect of thickness of energy director (EDs) and ultrasonic welding (USW) process parameters on structure formation and interlaminar shear strength (LSS) values of lap-joints of composite polyetheretherketone (PEEK) based plates reinforced with 40 wt. % short carbon fibers (SCF). The null hypothesis was the necessity of complete melting and extrusion of the EDs from the fusion zones to ensure the minimal presence of discontinuities at reaching the maximum LSS value. During the USW with a flat anvil, frictional heating developed primarily along the periphery of the fusion zones due to less strict constraint conditions. The rational process parameters were the ED thickness of 100 μm and the USW duration of 800 ms, which enabled the formation of the fusion zones over the 62.5 % of the contact region. The LSS values of >11 MPa with the load at failure of >4500 N developed through the base material due to bending of the adherends. The use of a spherical anvil localized frictional heating and fusion in the center of the clamped region. Without EDs, the lap joints achieved the maximum stress at failure of >60 MPa; however, the small fusion zone area limited their load-bearing capacities to 3000 N. The multi-spot lap-joints of the adherends from the PEEK/SCF composite formed without EDs were characterized by the structural integrity, while the stress at failure was equal to ~30.8 MPa, which were 2–3 times higher than those with the EDs 100 and 250 μm thick. The structure of the multi-spot-welded joints was determined by the ratio of the ED thickness to the distances between adjacent spots. Inserting the EDs significantly enlarged the fusion zone area, but uneven distributions of the clamping force resulted in their different melting and spreading patterns, giving rise to in discontinuities in the formed structure. The optimization of USW procedures for fibrous PEEK/SCF composites should be aimed at achieving a balance between the distances between adjacent spots and the ED thickness to ensure control of melting the polymer in fusion zones (outside the clamped region) and to eliminate the formation of discontinuities caused by its deficiency due to squeezing out.
Keywords: Ultrasonic welding; Polymer matrix composite; Polyetheretherketone; Short carbon fiber; Energy director; Interlaminar shear strength